Fertility preservation in female cancer patients in Brazil: perceptions and attitudes of infertility specialists - Ranniger, Renata Lack [UNESP]; Lamaita, Rivia Mara; D'Abreu, Barbara Flecha; Tolentino, Mariana Rodrigues; Candido, Eduardo Batista; Andrade, Warne Pedro [UNESP]; Nogueira-Rodrigues, Angelica; Silva-Filho, Agnaldo Lopes [UNESP] (Federacao Brasileira Soc Ginecologia & Obstetricia-febrasgo, 2024)
Objective: Fertility preservation is a priority in oncology for female cancer patients. However, there is a lack of communication between infertility specialists and oncologists. This study aimed to evaluate infertility specialists' perceptions and experiences regarding fertility preservation. Methods: Conduct an online survey to profile infertility specialists. Participants were infertility affiliated with the Brazilian Federation of Gynecology and Obstetrics Associations (FEBRASGO]. The specialists received an online survey, which response rate were 30.9%, most of whom were in southern and southeastern. The survey consisted on 14 questions about the infertility specialists' location, techniques in clinical practice, treatment successful rate, patients idea, etc. Results: The average experience in human reproduction were 15.5 +/- 10.2 years (mean +/- standard deviation, range 1-40]. Among reproductive-aged female cancer patients recommended for fertility preservation, 60.3 +/- 28.8% (range 10-100%] underwent preservation procedures. Main barriers were cost (41%], oncologists' knowledge or acceptance (35%] and accessibility (9%]. Most infertility specialists (58%] considered 40 years the limit for fertility preservation. Leukemia, lymphoma, breast and ovarian cancers were prioritized for fertility preservation, while lung, thyroid, gastric, and brain cancers were less relevant. Conclusion: This is the first Brazilian study about infertility specialists' perceptions on oncology patients access to fertility preservation. These patients primarily receive treatment in the public health system, while infertility specialists mainly work in the private healthcare. This healthcare mode is currently fragmented, but integrating these experts is enhancing patient access to fertility preservation. Studies on this topic are still warranted.
Keywords: Fertility preservation; Reproduction; Fertility; Neoplasms; Oocyte retrieval; Health knowledge, attitudes, practice; Gynecologists; Oncologists; Surveys; questionnaires